Comparing Authoritarian Publics: The Benefits and Risks of Three Types of Publics for Autocrats. Issue 2 (14th February 2020) - Toepfl, Florian
Abstract: Researchers comparing political communication across non-democratic contexts presently lack a widely acknowledged theoretical framework to guide their efforts. In order to fill in this gap, this essay develops a theoretical account that proposes comparing not authoritarian media systems, but "authoritarian publics." Drawing on theories of the multiple public sphere, two typologies are delineated: (a) a three-fold typology of partial publics, operating within authoritarian regimes and (b) a three-fold typology of "publics-at-large, " to be distinguished across authoritarian regimes. As it is argued, the publics-at-large of authoritarian regimes can be composed of three types of partial publics: (a) uncritical, (b) policy-critical, and (c) leadership-critical publics. With reference to political science literature about the emergence of formally democratic institutions in non-democratic regimes, critical publics are interpreted as institutions that help autocrats carry out important tasks. The benefits and risks associated with critical publics for autocrats are comparable to those of other pseudo-democratic institutions.